TDS exposure project: Application of the analytic hierarchy process for the prioritization of substances to be analyzed in a total diet study. (February 2015) - Papadopoulos, A.; Sioen, I.; Cubadda, F.; Ozer, H.; Oktay Basegmez, H.I.; Turrini, A.; Lopez Esteban, M.T.; Fernandez San Juan, P.M.; Sokolić-Mihalak, D.; Jurkovic, M.; De Henauw, S.; Aureli, F.; et al.
Highlights: Analytic Hierarchy Process has been applied in the framework of a TDS to obtain a priority list of substances. The ten first substances of highest interest are MeHg, Cd, As, Pb, Al, dioxins, PCBs, sulfites, acrylamide, BPA, and MOSH. The process is adjustable according to specificities of a country, emerging substances and new toxicological data. Abstract: The objective of this article is to develop a general method based on the analytic hierarchy process (AHP) methodology to rank the substances to be studied in a Total Diet Studies (TDS). This method was tested for different substances and groups of substances (N = 113), for which the TDS approach has been considered relevant. This work was performed by a group of 7 experts from different European countries representing their institutes, which are involved in the TDS EXPOSURE project. The AHP methodology is based on a score system taking into account experts' judgments quantified assigning comparative scores to the different identified issues. Hence, the 10 substances of highest interest in the framework of a TDS are trace elements (methylmercury, cadmium, inorganic arsenic, lead, aluminum, inorganic mercury), dioxins, furans and polychlorinated biphenyls (PCBs), and some additives (sulfites and nitrites). The priority list depends on both the national situation (geographical variations, consumer concern, etc.) and the availability of data. Thus, the list depends on the objectives of the TDS and on reachable analytical performances. Moreover, such a list is highly variable with time and new data (e.g. social context, vulnerable population groups, emerging substances, new toxicological data or health-based guidance values).